The tone of teachers’ melody and wellbeing in digital space - Mirzapour, Fatemeh; Şengül, Mehmet; Curle, Samantha (Frontiers in Education, 2025)
IntroductionEducational technology has become an essential element for improving education. To achieve this goal, teachers are required to have the necessary skills for integrating technology in their educational activities which in turn can be stressful for them. So, this phenomenological study aimed to investigate the positive and negative impacts of technology on teachers’ physical and social aspects of well-being.MethodsThe study was conducted with 12 teachers (seven females and five males) teaching in different high schools in Tabriz, Iran. Six had a BA, and six had a master’s degree with at least 5 years of teaching experience. Semi-structured interviews and a narrative frame were used to gather data. MAXQDA version 2022 was used to analyze the collected data.ResultsThe results revealed that implementing digital tools had positive and negative impacts on teachers’ physical and social well-being. Positive effects on physical well-being were saving time and energy, and brain activation, but exhaustion, increased health risk, and reduced productivity were the negative ones. Besides, teachers experienced positive social well-being, enabling communication among people across the globe, and easier access and transfer of information. Negative social well-being included adverse effects on child-family relationships and reduced face-to-face interaction.DiscussionTo develop healthy habit of technology use, teachers should have information regarding the positive and negative impacts of technology on their physical and social well-being.